The 536C→T Transition in the Human Tissue Factor Pathway Inhibitor (TFPI) Gene Is Statistically Associated with a Higher Risk for Venous Thrombosis - Kleesiek, Knut; Schmidt, Michael; Götting, Christian; Schwenz, Britt; Lange, Stefan; Müller-Berghaus, Gert; Brinkmann, Thomas; Prohaska, Wolfgang (Thrombosis and Haemostasis, 1999)
Tissue factor pathway inhibitor (TFPI) is an important regulator in the extrinsic blood coagulation pathway. Although the regulatory biochemical role of TFPI is evident, the clinical significance of this proteinase inhibitor remains to be elucidated. The definition of a clinical TFPI deficiency seems to be more complex than that of other coagulation inhibitors because the activity and concentration of circulating TFPI can not be considered a true measure of in vivo levels. Its determination in plasma samples by immunological methods or functional assays has been shown to be inadequate in the detection of a clinical deficiency.Therefore, we screened genomic DNA samples of blood donors and thrombotic patients for alterations in the TFPI gene to assess the influence of a modified TFPI in venous thromboembolic diseases. We detected a single nucleotide substitution in exon 7 (536C→T) leading to a proline to leucine exchange at amino acid position 151 of the protein ([P151L]TFPI) and found the prevalence of heterozygous carriers in German unrelated blood donors to be 0.2% (n = 5120).Four unrelated persons out of 14 probands carrying the genetic variation could be linked to venous thrombosis. For calculation of a potential risk for venous thrombosis for carriers of the mutation we investigated healthy blood donors about thrombotic events. 7 out of 308 blood donors were found to have a history of venous thrombosis, one of them carried the TFPI mutation. Statistical calculation showed a significant relative risk for venous thrombosis for individuals with the trait (odds ratio, 9.3; confidence interval, 1.8-48.6; p <0.01).